Implementation of Contract Hybrid Concept in Multi Services Products (Aplication of the Warranty Bank Products/Kafalah in Syariah Banks) - Muhammad Firmansyah (UIN Sunan Gunung Djati Bandung, 2016)
Product of multi services in sharia banks presented in order to meet the needs of society as well as the development of the era transactions that course in accordance with Islamic principles, then the ownership in the syariah products including multi product in Islamic banking services using the concept of multi akad therein. This is done so that innovation in Islamic banking products had been developed so that it can be chosen by the public in conducting business transactions. Likewise, the multi-service bank guarantee products in Islamic banking, is a multi product contract, where there is more than one contract. Bank guarantees in Islamic banking is generally called kafalah product because this product is Kafalah main contract, followed by Ijarah contract, wadiah, and qardh. This paper examines the concept of multi-contract/contract executed hybrid shariah banking at bank product warranty/kafalah